1979
DOI: 10.1071/bt9790833
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Vegetation at Kosciusko. III. Alpine Range Transects, 1959-1978

Abstract: Measurements of overlapping cover of plant species on permanent transects between 1959 and 1978 in the alpine tract at two sites near Kosciusko and Gungartan generally confirm an earlier hypothesis that the cover at Kosciusko, after 15 years' protection from grazing and burning (i.e, by 1959), had attained a degree of equilibrium. A long-term cycle of first decrease and then increase was measured in the cover of the dominant snowgrasses (Poa) and a few other species. Small colonizing species (notably Neopaxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 0 publications
3
23
1
Order By: Relevance
“…By 1825, herds of up to 800 cattle were grazing on grasslands adjacent to Great Lake (Wedge 1825, in Crawford et al 1962) and by the late nineteenth century, approximately 350 000 sheep were seasonally pastured around the lakes of the Central Plateau (Shepherd 1973). Furthermore, recent studies have confirmed the long-lasting, deleterious effects of grazing in high altitude grassy ecosystems (Wimbush & Costin 1979;Leigh et al 1987;Gibson & Kirkpatrick 1989). Also, exotic pollen such as Pinus radiata, Plantago lanceolata and Taraxacum are restricted to Zone 1.…”
Section: Vegetation Historymentioning
confidence: 84%
“…By 1825, herds of up to 800 cattle were grazing on grasslands adjacent to Great Lake (Wedge 1825, in Crawford et al 1962) and by the late nineteenth century, approximately 350 000 sheep were seasonally pastured around the lakes of the Central Plateau (Shepherd 1973). Furthermore, recent studies have confirmed the long-lasting, deleterious effects of grazing in high altitude grassy ecosystems (Wimbush & Costin 1979;Leigh et al 1987;Gibson & Kirkpatrick 1989). Also, exotic pollen such as Pinus radiata, Plantago lanceolata and Taraxacum are restricted to Zone 1.…”
Section: Vegetation Historymentioning
confidence: 84%
“…Nonetheless, fifteen years after fire, an alpine herbfield was well developed, with less than 5% bare ground (Ashton and Williams, 1989;Wimbush and Costin, 1979c). The rate and extent of response varies according to disturbance history (fire and grazing) and there was 12% bare ground in herbfields some twenty years after fire (Wimbush and Costin, 1979c). Shrubs can establish in herbfields that have been burnt and/or grazed but may decline in abundance in the absence of further disturbance (Carr, 1977;Costin et al, 1959).…”
Section: Effects Of Management (Fire and Grazing) On Alpine Herbfieldsmentioning
confidence: 98%
“…Shrubs can establish in herbfields that have been burnt and/or grazed but may decline in abundance in the absence of further disturbance (Carr, 1977;Costin et al, 1959). Twenty years after removal of fire and grazing, some herbfields retained a shrub cover of less than 4% (Wimbush and Costin, 1979c). Shelter and deeper soils help herbfield species establish (Costin et al, 1969).…”
Section: Effects Of Management (Fire and Grazing) On Alpine Herbfieldsmentioning
confidence: 99%
“…This may be an artifact of the dominance of these species over the more natural, but less common fen vegetation. Wimbush and Costin (1979b) have recorded that insect damage can cause the death of some plants. Factors like this must also be considered when looking at the stresses imposed on plants when the habitat is drastically altered, as by addition of sewage effluent.…”
Section: Vegetation Surveys and Nutrient Analysesmentioning
confidence: 99%